Historical Development over Religious Liberty in the Indonesian Constitution - Mahaarum Kusuma Pertiwi (Fakultas Hukum, Universitas Warmadewa, 2020)
This paper finding is the existence of recurring unsettled negotiation between the Islamists and the Nationalists during three important constitutional works in Indonesia (the making of 1945 Constitution; the work of Konstituante to draft a new constitution in 1955-1959; and the constitutional amendment 1999-2002). Such fragile political consensus creates a legal gap in the Indonesian legal system: constitutional guarantee on religious liberty on one hand, and discriminative derivative laws and court decisions in relate to religious liberty on the other hand. This paper argues the legal gap happens because historically, discourse over religious liberty never settled during constitutional debates. It leads to ambiguous constitutional articles on religious liberty such as the seemingly contradicting Article 28 I (1) on absolute rights and Article 28 J (2) on the limitation of rights. The ambiguous constitutional articles give no solid basis for protecting religious liberty, especially for minority, although explicitly Article 29 (2) of the Constitution stating, ‘The State guarantees freedom of every inhabitant to embrace his/ her respective religion and to worship according to his/ her religion and faith as such’. This paper will explain the unsettled negotiations during the making of Pancasila and the Jakarta Charter in 1945; the debate within Konstituante’s work in 1959; and the debate during constitutional amendment in 1999-2002.